Impact Dipping Pyramidal-Prismatic Piles and their Resistance to Pressure and Horizontal Load - Bekbasarov, Isabai; Shanshabayev, Nurzhan (Periodica Polytechnica Civil Engineering, 2021)
The results of experiments carried out in the field with the use of large-scale models of reinforced concrete driven pyramidal - prismatic piles with different lengths of the pyramidal part are presented. The impact capacity of piles were evaluated of their bearing capacity to the action of indentation and horizontal static loads. It has been established that the driving of pyramidal-prismatic piles is accompanied by both large (by10–1.60 times) and lower (by 8.0–37.0 %) energy consumption for their driving in comparison with conventional pris-matic and pyramidal piles. It was also revealed that under the action of a vertical indentation load, the bearing capacity of the pyramidal-prismatic piles is09–1.48 times, and under the action of a horizontal static load, it is17–1.80 times higher than that of a prismatic pile. It has been established that with an increase in the length of the pyramidal part of the test piles, there is an increase in their bearing capacity by12–1.34 times. Formulas are proposed for determining the bearing capacity of pyramidal-prismatic piles. The research results serve as the basis for the development of recommendations for the calculation and design of pyramidal-prismatic piles.